Reinventing Licentiousness : Pornography and Modern China - Wang, Y. Yvon, 1986- (Book collections on Project MUSE., 2021)
"Uses Beijing police archives to present a social and intellectual history of the evolution of markets for and regulation of sexual depictions in today's China, focusing on media markets from c. 1880 to 1940 as a motor for cultural change and linking the Chinese case to global trends"--